UPAYA PT RAPP DALAM PELAKSANAAN TUJUAN PEMBANGUNAN BERKELANJUTAN (TPB) MENGENAI EKOSISTEM DARAT DI SEKTOR TESO TIMUR - Bella Cristine Rodelia Hutauruk; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT The issue of deforestation has become a major concern since a decade ago. This is one of the reasons why Terrestrial Ecosystems are a focus of the UN's Sustainable Development Goals program. Based on the increasing recognition by business actors of multinational companies operating in the natural resources sector, it is necessary to manage operational risk and their reputation on environmental issues such as water scarcity, pollution, climate change and loss of biodiversity. PT. RAPP as a multinational company also participates in implementing the United Nations Sustainable Development Goals through corporate social responsibility (CSR) activities. In this study, researchers used a constructivism perspective, with the theory of corporate social responsibility (CSR) as a basic reference for research. Data were obtained from journals, official websites, books, and interviews and observations at one of the multinational companies in Indonesia, namely PT RAPP. The results of the study show that PT RAPP as a multinational company engaged in the pulp and paper industry implements a thriving landscape. PT RAPP in the East Teso sector carries out efforts to protect and preserve its forests with the target of implementing the Sustainable Development Goals on Terrestrial Ecosystems through zero net loss conservation, biodiversity and wildlife protection activities, in which this CSR intends to obtain standardization from the International Standardization Organization, namely ISO 14001. Keywords: Land Ecosystems, Multinational Companies, SDGs, CSR